Species consumed by goats in Sierra La Laguna, Baja California Sur - Salgado-Beltrán, Victor Abrahán; Murillo Amador, Bernardo; Nieto-Garibay, Alejandra; Aguilera-Marín, Narciso; Ortega Pérez, Ricardo (Ecosistemas y Recursos Agropecuarios, 2020)
The local knowledge of the wild species that goats consume in the areas surrounding the natural reserves contributes to the establishment of op- tions for livestock production systems associated to the semiarid zones, with a focus on the preservation of the species, the economy of the farmers and the safeguarding of the environment. The objective was to develop a quantitative method to evaluate the forage importance index of these species (based on empirical knowledge), defined as the primary function played by a species of goat plant in the goat farmers culture in an area of buffering of the Sierra La Laguna Biosphere Reserve in Baja California Sur. Seventeen random surveys were carried out to develop the method and calculate the Forage Importance Index (FII) of the species, using eight indices (Abundance Perception Index, Frequency of Use Index, Consumed Organs Index, Consumption Season Index, Category Food and Index of Climatological Conditions) as well as the Salience Index and the Mention of Frequency. There were 37 species of plants associated with the area, the most abundant by family are 10 Fabaceaes, 4 Cactacea, 4 Euphorbiaceaes and 3 Asteraceaes. The most mentioned species include vinorama (Acacia farnesiana), palo zorrillo (Cassia emarginata), palo verde (Cercidium floridum) and ironwood (Pithecollobium confine).The five species with the highest value of FII include vinorama (Acacia farnesiana), palo zorrillo (Cassia emarginata), palo verde (Cercidium floridum), ironwood (Pithecollobium confine) and palo eva (Pithecellobium undulatum).